2006
DOI: 10.1590/2175-7860200657102
|View full text |Cite
|
Sign up to set email alerts
|

Tricomas Foliares Em Espécies De Croton L. (Crotonoideae-Euphorbiaceae)

Abstract: RESUMO Foi realizado estudo da ultraestrutura dos tricomas foliares em microscopia eletrônica de varredura (MEV) de 14 espécies do gênero Croton, ocorrentes nas zonas do litoral e da mata do estado de Pernambuco, com o objetivo de caracterizar morfologicamente cada tipo de tricoma, como recurso auxiliar na delimitação das espécies e ainda relacionálos à classificação de Webster. Foram registrados 10 tipos de tricomas: estrelado-porrecto, fasciculado, multiradiado, dendrítico, lepidoto, estrelado-rotado, estrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…Various types of non-glandular pluricellular trichomes are frequently mentioned and recognized as a relevant taxonomic character for Croton constituting important elements in the recognition of the genus and in the characterization of species (Metcalfe & Chalk, 1950;Webster et al 1996). In the plants analyzed here, we found that the different morphologies of non-secreting trichomes can actually applied in their recognition, corroborating the proposals of other authors who also point out the use of these appendages in the delimitation of clades or in phylogenetic approaches (Lucena & Sales, 2006;Riina et al, 2009). Trichome-like emergences were investigated by Vitarelli, Riina, Cassino, and Meira (2016) Colleters are important secretory structures, especially for producing secretions that protect young leaves.…”
Section: Discussionsupporting
confidence: 89%
“…Various types of non-glandular pluricellular trichomes are frequently mentioned and recognized as a relevant taxonomic character for Croton constituting important elements in the recognition of the genus and in the characterization of species (Metcalfe & Chalk, 1950;Webster et al 1996). In the plants analyzed here, we found that the different morphologies of non-secreting trichomes can actually applied in their recognition, corroborating the proposals of other authors who also point out the use of these appendages in the delimitation of clades or in phylogenetic approaches (Lucena & Sales, 2006;Riina et al, 2009). Trichome-like emergences were investigated by Vitarelli, Riina, Cassino, and Meira (2016) Colleters are important secretory structures, especially for producing secretions that protect young leaves.…”
Section: Discussionsupporting
confidence: 89%
“…respectively; the multiradiate trichomes of C. hatschbachii were likewise observed in taxa belonging to the sections Barhamia, Cyclostigma, and Geiseleria by Gordillo & Matías (2005), Feio et al (2018), and Sodré et al (2019) respectively. Similarly, the stellateporrect trichomes observed here in C. campestris and C. subvillosus, seem to be the most frequent in the genus (e.g., Lucena & Sales 2006;Carneiro-Torres et al 2011;Feio et al 2018). We also highlight the structures interpreted here as trichomes truly represent those structures -unlike structures with similar appearances reported for other species of the genus by Vitarelli et al (2016) and Sodré et al (2019), which are simply trichome-like emergences, not found in the species here studied.…”
Section: Leaf Anatomysupporting
confidence: 82%
“…2), as was reported by Barros & Soares (2013) and Vitarelli et al (2015) for other Croton species. Among these features, the types of trichomes can be highlighted, as they have been used to differentiate species in the genus even since Müller Argoviensis (1873), and were emphasized by Webster et al (1996) and other authors such as Inamdar & Gangadhara (1977), Nepumoceno & Oliveira (1979) and Lucena & Sales (2006). Despite the taxonomic value of the trichomes in some cases at both sectional and species levels, we emphasize that different type of trichomes appear to have evolved independently within the genus, as they occur in taxa from distinct sections.…”
Section: Leaf Anatomymentioning
confidence: 99%
“…In C. rhamnifolius and C. rhamnifolioides were verified dendritic and glandular trichomes, 31 in C. cajucara was identified the multiradiate trichome, 37 while in C. cordiifolius is seen stellate, simple and glandular trichomes. Lucena and Sales 38 have characterized the types of trichomes presents in leaf blade of 14 species of Croton as stellate, fasciculate, multiradiate, dendritic, lepidote, simple and glandular. The authors have stated that the type of trichome is an important feature for the taxonomy of the genus.…”
Section: Anatomical Characterizationmentioning
confidence: 99%